Finite element analysis of optimized novel additively manufactured non-articulating prostheses for cervical total disc replacement - Hsieh, Ming-Kai; Tai, Ching-Lung; Li, Yun-Da; Lee, De-Mei; Lin, Cheng-Yi; Tsai, Tsung-Ting; Lai, Po-Liang; Chen, Weng-Pin (Frontiers in Bioengineering and Biotechnology, 2023)
Ball-and-socket designs of cervical total disc replacement (TDR) have been popular in recent years despite the disadvantages of polyethylene wear, heterotrophic ossification, increased facet contact force, and implant subsidence. In this study, a non-articulating, additively manufactured hybrid TDR with an ultra-high molecular weight polyethylene core and polycarbonate urethane (PCU) fiber jacket, was designed to mimic the motion of normal discs. A finite element (FE) study was conducted to optimize the lattice structure and assess the biomechanical performance of this new generation TDR with an intact disc and a commercial ball-and-socket Baguera®C TDR (Spineart SA, Geneva, Switzerland) on an intact C5-6 cervical spinal model. The lattice structure of the PCU fiber was constructed using the Tesseract or the Cross structures from the IntraLattice model in the Rhino software (McNeel North America, Seattle, WA) to create the hybrid I and hybrid II groups, respectively. The circumferential area of the PCU fiber was divided into three regions (anterior, lateral and posterior), and the cellular structures were adjusted. Optimal cellular distributions and structures were A2L5P2 in the hybrid I and A2L7P3 in the hybrid II groups. All but one of the maximum von Mises stresses were within the yield strength of the PCU material. The range of motions, facet joint stress, C6 vertebral superior endplate stress and path of instantaneous center of rotation of the hybrid I and II groups were closer to those of the intact group than those of the Baguera®C group under 100 N follower load and pure moment of 1.5 Nm in four different planar motions. Restoration of normal cervical spinal kinematics and prevention of implant subsidence could be observed from the FE analysis results. Superior stress distribution in the PCU fiber and core in the hybrid II group revealed that the Cross lattice structure of a PCU fiber jacket could be a choice for a next-generation TDR. This promising outcome suggests the feasibility of implanting an additively manufactured multi-material artificial disc that allows for better physiological motion than the current ball-and-socket design.